Assessment of defecation function after sphincter-saving resection for mid to low rectal cancer: A cross-sectional study. (December 2021) - Luo, Bao-Jia; Zheng, Mei-Chun; Xia, Yang; Ying, Zhu; Peng, Jian-Hong; Li, Li-Ren; Pan, Zhi-Zhong; Qin, Hui-Ying
Abstract: Purpose: Patients with mid-to low-rectal cancer can have various dysfunctions of defecation after sphincter-saving resection. Defecation dysfunction can manifest as incontinence, urgency, or frequent bowel movements, and is called low anterior resection syndrome (LARS). This study aimed to examine LARS score and objective anorectal function indices in Chinese patients receiving sphincter-saving surgery for mid-to low-rectal cancer. Method: This was a single-center cross-sectional study of patients undergoing sphincter-saving resection for low- or mid-rectal cancer and had restoration of trans-anal defecation for at least 1 month seen between January 2019 and June 2020. Patients completed a questionnaire regarding clinical characteristics, and Low Anterior Resection Syndrome (LARS) score and high-resolution anorectal manometry (HR-ARM) were used to assess defecation function. Multivariable analysis was used to identify variables significantly associated with defecation dysfunction. Results: 146 patients completed and returned the questionnaires. 25 healthy adults also participated as control group for the anorectal manometry. Approximately 76% of patients developed LARS after surgery, of which 35.6% had major LARS. In these patients, anorectal manometry indices including initial rectal sensory capacity and rectal fecal sensory capacity, were significantly lower than normal. Logistic regression analysis showed that preoperative chemo-radiotherapy and the tumor inferior margins being close to the dentate line, especially 2–5 cm, were independent risk factors for defecation dysfunction after surgery. Conclusions: Defecation dysfunction is a frequent occurrence after sphincter-saving resection for mid- and low-rectal cancer. Preoperative chemo-radiotherapy and a shorter tumor inferior margins distance to the dentate line are independent factors for defecation dysfunction. Highlights: A comprehensive evaluation of defecation function was done. We examine the incidence of LARS and the HR-ARM parameters of the patients. Preoperative chemo-radiotherapy increased the risk of defecation dysfunction. Tumor inferior margin next to dentate line was a risk factor of defecation disorder.